Virtual reality-guided left ventricular assist device implantation in pediatric patient: Valuable presurgical tool - Rajesh Kumar Ramaswamy; Sathish Kumar Marimuthu; Krishna Kumar Ramarathnam; Srinath Vijayasekharan; Kemundel Genny Suresh Rao; Komarakshi R Balakrishnan (Wolters Kluwer Medknow Publications, 2021)
Virtual reality (VR) is increasingly used for presurgical planning and teaching during surgery. However, VR aided presurgical planning toolbox for left ventricular assist device (LVAD) implantation is not widely available. We investigated the use of a VR environment with wearable headsets and touch controllers in simulating an implant in an 11-year-old boy. The technology played a significant role in the optimal positioning of the LVAD.